Transactional leadership and intellectual capital, the mediating role of knowledge sharing: The study of customs employees in Sulaymaniyah governorate - Doste Khoshnaw; Georgiana Karadaş (Heliyon, 2024)
This study aims to examine the impact of transactional leadership style on intellectual capital, and knowledge sharing as a mediator between transactional leadership and each of the intellectual capital components (human capital, structural capital, and relational capital) in the public sector, in Sulaymaniyah governorate in north of Iraq. The research model was settled based on the previous investigations on transactional leadership, knowledge sharing, and intellectual capital. To collect the data, convenience sampling was utilized, questionnaires were sent to employees in five customs directorates, and 355 responses were received. The research model analytical estimation was conducted through the employment of (SEM) Structural Equation Modeling by using Partial Least Square (PLS). The findings of the research show that transactional leadership has a significant relationship with knowledge sharing as well as with all three components of intellectual capital. Knowledge sharing also has a significant correlation with the components of intellectual capital. Moreover, the study's results show that knowledge sharing mediates the relationship between transactional leadership with human capital, structural capital, and relational capital.